Effect of Environmental Chemical Stress on Nuclear Noncoding RNA Involved in Epigenetic Control. (3rd August 2015) - Arrigo, Patrizio; Pulliero, Alessandra
Abstract : In the last decade the role of noncoding RNAs (ncRNAs) emerges not only as key elements of posttranscriptional gene silencing, but also as important players of epigenetic regulation. New kind and new functions of ncRNAs are continuously discovered and one of their most important roles is the mediation of environmental signals, both physical and chemical. The activity of cytoplasmic short ncRNA is extensively studied, in spite of the fact that their function and role in the nuclear compartment are not yet completely unraveled. Cellular nucleus contains a multiplicity of long and short ncRNAs controlling at different levels transcriptional and epigenetic processes. In addition, some ncRNAs are involved in RNA editing and quality control. In this paper we review the existing knowledge dealing with how chemical stressors can influence the functionality of short nuclear ncRNAs. Furthermore, we perform bioinformatics analyses indicating that chemical environmental stressors not only induce DNA damage but also influence the mechanism of ncRNAs production and control.